Performing more than 20 purposeful gameplay headers in a soccer season may alter autonomic function in female youth soccer players - Bonn, M. M.; Harriss, A. B.; Thompson, J. W. G.; Dickey, J. P. (Research in Sports Medicine, 2021)
This study evaluated the effects of cumulative purposeful soccer heading on autonomic nervous system function in 22 female youth soccer players (13.3±0.9years). A 10 minute electrocardiogram recording was collected at baseline and following the 20 game season (post-season) to calculate measures of heart rate variability (HRV), including standard deviation of the normal-normal intervals, total power, high frequency (HF), low frequency (LF), LF:HF, normalized HF and normalized LF. Participants were categorized into low- (<20 headers per season; n =13) and high- (>20 headers per season; n =9) exposure groups. Mann-Whitney U tests demonstrated no significant differences between groups for any HRV metric. However, the increased normalized LF power (low exposure 8.67 and high exposure -31.17, respectively; r =0.35) and LF:HF power (-6.39 and 15.80, respectively; r =0.35), between groups had moderate practical significance. Therefore, female youth players who perform more than 20 purposeful headers during a soccer season may exhibit altered autonomic function.